La dépluralisation en français dans une perspective comparative - Sorbet, Piotr (Verbum – Analecta Neolatina, 2024)
The aim of this study is to describe the cases of depluralized forms in French. This occurs in two different situations. First of all, these are the historical forms of words in which the markers of plurality lose this value, which leads to the addition of a new plural mark. Secondly, depluralization occurs during lexical borrowing where the imported form which expresses the plural is not felt as such by the speakers of the borrowing language, which leads them to attach a new plural mark. Given that depluralization is treated in various ways, we look not only at French forms but we start from a more complex perspective. This takes into account depluralization in several languages, but we also deal with terminological questions and we indicate the main differences between depluralization, singularization and the double plural.